2017
DOI: 10.1371/journal.pone.0178091
|View full text |Cite|
|
Sign up to set email alerts
|

Does NGAL reduce costs? A cost analysis of urine NGAL (uNGAL) & serum creatinine (sCr) for acute kidney injury (AKI) diagnosis

Abstract: IntroductionUrine neutrophil gelatinase-associated lipocalin (uNGAL) is a sensitive and specific diagnostic test for acute kidney injury (AKI) in the Emergency Department (ED), but its economic impact has not been investigated. We hypothesized that uNGAL used in combination with serum creatinine (sCr) would reduce costs in the management of AKI in patients presenting to the ED in comparison to using sCr alone.Materials and methodsA cost simulation model was developed for clinical algorithms to diagnose AKI bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…H-FABP, associated with cardiac injury, is released into the bloodstream 30 min after an ischaemic event and peaks at 6 h before returning to normal levels after 24 h 32 . H-FABP has been reported to predict AKI pre and post cardiac surgery 7,11,33 however, this is the first time that H-FABP has been demonstrated to predict AKI in patients pre and post ORIF surgery. H-FABP is predominantly expressed in the heart but also at lower levels in skeletal muscle, kidney, stomach, brain and testis 34,35 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…H-FABP, associated with cardiac injury, is released into the bloodstream 30 min after an ischaemic event and peaks at 6 h before returning to normal levels after 24 h 32 . H-FABP has been reported to predict AKI pre and post cardiac surgery 7,11,33 however, this is the first time that H-FABP has been demonstrated to predict AKI in patients pre and post ORIF surgery. H-FABP is predominantly expressed in the heart but also at lower levels in skeletal muscle, kidney, stomach, brain and testis 34,35 .…”
Section: Discussionmentioning
confidence: 82%
“…Creatinine measured in serum or plasma is the most commonly used biomarker to determine estimated glomerular filtration rate (eGFR). However, an increase in creatinine levels after renal insult is often delayed and a change in plasma creatinine levels may not be evident until two to three days after the initial insult 7 . Work in animals and humans has shown that although AKI due to ischemia can be prevented and treated, preventative therapy must be started very early after the renal injury 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Various studies (Gungor et al, 2014;Haase et al, 2009;Ralib et al, 2014;Shyam et al, 2017;Wang et al, 2014;Yang et al, 2014) have demonstrated that NGAL could be used in the prediction of mortality. Parikh et al (2017) showed that there is a considerable increase in the NGAL levels after shock (circulatory) in the patients undergoing intensive care. It was stated that NGAL could be used for predicting the development of AKI before one to three days according to creatinine level; therefore, it would serve as a suitable early descriptive biomarker for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…The administration of nephrotoxic medications in such patients is discontinued, fluid overload is avoided, and early decision on the indications for the initiation of renal replacement therapy is taken if the sCr level rises as well [5]. Early recognition of renal damage, application of preventive measures, and initiation of adequate treatment are of crucial importance in order to avoid the development of AKI, to reduce pediatric mortality and treatment costs, and to improve disease outcomes [5,36].…”
Section: Discussionmentioning
confidence: 99%